Hubungan Kejadian Hipertensi dengan Kadar Trigliserida pada Supir Bus di Terminal Arjosari Kota Malang - Diki, Asrini Rambu; Fatmawati, Diana Noor; Husnah, Yeni Avidhatul (Jaringan Laboratorium Medis, 2024)
Hypertension is a health problem that is widely encountered in the community and correlates with other diseases. There are many factors that cause hypertension, one of which is abnormal triglyceride levels or hypertriglycerides. Higher levels of triglycerides will inhibit the occurrence of lipogenesis. Lipogenesis is a factor that causes hypertension from food intake, this is because food has a significant role in increasing blood pressure, especially protein and fat. This study aims to determine the relationship between triglyceride levels and hypertension. This type of research is an analytical research with the crosssectional method, statistical data analysis using correlation regression, the number of population as many as 50 respondents and the sample used as many as 21 respondents. Data collection using questionnaires, blood pressure measurements and triglyceride level checks. Blood pressure measurement is done manually and then for the examination of triglyceride levels using the GPO-PAP method is carried out in the laboratory of the Bareng Health Center using a spectrophotometer. The statistical analysis used is the correlation Pearson test. The results of the study on bus drivers with high blood pressure showed that some respondents had high triglyceride levels because they often ate fatty foods. Based on the examination that has been carried out on 21 bus driver respondents at the Arjosari Terminal, Malang City, it shows that triglyceride levels and high blood pressure have no relationship, with the test results using the Pearson correlation statistical test obtained a result of P=0.0766 >0.05 with a Pearson value of P=-0.069 correlation meaning that it does not have a relationship with the degree of very weak relationship.